Avaliação das Boas Práticas de Fabricação de cachaça de alambique no Estado da Bahia como suporte para desenvolvimento biotecnológico dos processos produtivos da bebida - Goncalves, Cleber Miranda (2009)
The “cachaça” is a product of growing economic importance and wide acceptance in the national and international market. This alcoholic beverage was elevated to the rank of noble beverage, a national symbol, and is the third most consumed distilled beverage in the world. The “cachaça” is a beverage that has a characteristic flavor and aroma which are guaranteed with the use of better raw material, without burning the sugar cane and natural fermentation. The evaluation of Good Manufacturing Practices (GMP) of the productive chain of “cachaça” in Bahia through the check-list is an important instrument for the verification of the hygienic-sanitary quality of the drink. This work has as an objective to develop and implement a check-list to assess the GMP in the productive chain of the “cachaça” in the state of Bahia. The check-list used to verify the GMP is formed by a total of 194 items of verification. This guide of verification deals with the items that allow one to value and define corrective actions for adequate cleanliness of internal and external areas of the facilities, the sanitary practices adopted in the production, cleaning and disinfecting the facilities, equipment and utensils, sanitary-hygienic aspects of equipment and utensils, employee hygiene, the stages of producing the drink and the guarantee of systems of quality of the beverage. A scale was adopted to consider the total weight which allows the establishment to be classified as "Excellent", "Very good", "Good", "Regular" or "Bad”. Where researched and analyzed, 100 producers of “cachaça” in the state of Bahia. Of these, 10 (10.0 %) producers were classified as "Good", 9 (9.0 %) producers were classified as "Regular" and 81 (81.0%) producers were classified as "Bad" according to the total weight distributed by the check-list.